ANALISIS KEBIJAKAN INDO-PASIFIK AMERIKA SERIKAT DAN CINA TERHADAP INDONESAI DALAM MENDUKUNG GAGASAN POROS MARITIM DUNIA - Nada Novia Puteri; Afrimadona; Laode Muhammad Fathun (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2022)
The Indo-Pacific region creates a new form of dynamics in the international world order, one of the two important situations in which is the rivalry between the US and China, and Indonesia with changes in its foreign policy, named World Maritime Axis. This grand concept under Joko Widodo administration intends to make Indonesia not only a maritime country but a world maritime power. Indonesia's strategic location, which is right in the middle of the Indian and Pacific Oceans and its central role in ASEAN, makes Indonesia one of the countries prioritized by the US and China in